Winners and losers of national and global efforts to reconcile agricultural intensification and biodiversity conservation - Egli, Lukas; Meyer, Carsten; Scherber, Christoph; Kreft, Holger; Tscharntke, Teja (Global change biology, 2018)
Closing yield gaps within existing croplands, and thereby avoiding further habitat conversions, is a prominently and controversially discussed strategy to meet the rising demand for agricultural products, while minimizing biodiversity impacts. The agricultural intensification associated with such a strategy poses additional threats to biodiversity within agricultural landscapes. The uneven spatial distribution of both yield gaps and biodiversity provides opportunities for reconciling agricultural intensification and biodiversity conservation through spatially optimized intensification. Here, we integrate distribution and habitat information for almost 20,000 vertebrate species with land‐cover and land‐use datasets. We estimate that projected agricultural intensification between 2000 and 2040 would reduce the global biodiversity value of agricultural lands by 11%, relative to 2000. Contrasting these projections with spatial land‐use optimization scenarios reveals that 88% of projected biodiversity loss could be avoided through globally coordinated land‐use planning, implying huge efficiency gains through international cooperation. However, global‐scale optimization also implies a highly uneven distribution of costs and benefits, resulting in distinct “winners and losers” in terms of national economic development, food security, food sovereignty or conservation. Given conflicting national interests and lacking effective governance mechanisms to guarantee equitable compensation of losers, multinational land‐use optimization seems politically unlikely. In turn, 61% of projected biodiversity loss could be avoided through nationally focused optimization, and 33% through optimization within just 10 countries. Targeted efforts to improve the capacity for integrated land‐use planning for sustainable intensification especially in these countries, including the strengthening of institutions that can arbitrate subnational land‐use conflicts, may offer an effective, yet politically feasible, avenue to better reconcile future trade‐offs between agriculture and conservation. The efficiency gains of optimization remained robust when assuming that yields could only be increased to 80% of their potential. Our results highlight the need to better integrate real‐world governance, political and economic challenges into sustainable development and global change mitigation research. Closing yield gaps within existing croplands poses additional threats to biodiversity within agricultural landscapes. We estimate that projected agricultural intensification between 2000 and 2040 would reduce the global biodiversity value of agricultural lands by 11%, relative to 2000. Around 88% or 61% of this biodiversity loss could be avoided through globally or nationally coordinated land‐use optimization, and 33% through optimization within just 10 countries. While global‐scale optimization implies a highly uneven distribution of costs and benefits, targeted efforts to improve the capacity for integrated land‐use planning on the national level may offer an effective avenue to better reconcile intensification‐biodiversity trade‐offs.